Pengembangan Inovasi Smart Aeroponik sebagai Upaya Efisiensi Urban Farming Produktif Ramah Energi - Rifandi, Raditya Ahmad; Putra, Rizal Ichsan Syah; Elawati, Nunung Eni; Yuliyani, Dwi Nur; Dafa Anwarul Fahmi (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
This article explores the development and application of smart aeroponic innovation as an effort to improve efficiency in energy-friendly urban farming. Smart aeroponics, which utilizes sensor technology and automatic control systems, is designed to maximize plant growth while minimizing energy and water use. In this community service project, we implemented a smart aeroponic system in several urban locations and trained local communities in its operation and maintenance. Evaluation of the results showed that this system can increase energy efficiency by up to 70% when compared to hydroponics with the Deep Flow Technique (DFT) method or each can save 29.02 kWh for mustard greens cultivation. And 41.00 kWh for lettuce cultivation. The potential of this technology is an effort to improve the efficiency of urban agriculture, but also provides significant ecological and economic benefits for urban communities, so that it can be a sustainable model for future agricultural development.